Clinical, histological and immunophenotypic findings in a mare with a mammary lymphoma associated with anaemia and pruritus - Mendes, Luiz Claudio Nogueira [UNESP]; de Araujo, M. A. [UNESP]; Bovino, F. [UNESP]; Rozza, Daniela Bernadete [UNESP]; Machado, Gisele Fabrino [UNESP]; Cadioli, Fabiano Antonio [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP]; Peiró, Juliana Regina [UNESP] (Wiley-Blackwell, 2011)
An 18-year-old Quarter Horse mare presented with an 18 week history of dermatological lesions characterised by recurrent urticaria and recent signs of enlarged mammary glands, pyrexia, alopecia and intense pruritus. Haematological and serum biochemical analyses revealed anaemia, leucocytosis, thrombocytopenia and hyperfibrinogenaemia. Mammary discharge was evaluated and revealed neutrophilia. Cytological examinations of fine needle aspirates from the parotid lymph nodes were normal. Common causes of anaemia were ruled out by specific tests. The initial diagnosis was mastitis and 2 weeks later the animal returned to the hospital with worsening of clinical signs, intermittent fever, intense pruritus and generalised alopecia. Blood samples were collected for haematological and serum biochemical analyses, and the mammary gland and parotid lymph nodes were biopsied. Rectal palpation revealed a large irregular mass near the left kidney with adhesions of surrounding structures. The animal died before the laboratory results were ready. This report details the clinical, histological and immunophenotypic findings of a case of large lymphoma in a mare.
Keywords: horse; mastitis; lymph nodes; immunohistochemistry; T cells